2016
DOI: 10.1589/jpts.28.2731
|View full text |Cite
|
Sign up to set email alerts
|

Association of ACTN3 polymorphisms with BMD, and physical fitness of elderly women

Abstract: [Purpose] Association of ACTN3 polymorphism with bone mineral density and the physical fitness of elderly women is still unclear. Therefore, this study investigated the association between ACTN3 genotype and bone mineral density, and the physical fitness of elderly women. [Subjects and Methods] Sixty-eight elderly women (67.38 ± 3.68 years) were recruited at a Seongbuk-Gu (Seoul, Korea) Medical Service Public Health Center. Measurements of physical fitness included muscle strength, muscle endurance, flexibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 23 publications
(26 reference statements)
1
15
0
Order By: Relevance
“…In the combined analysis of genes, improved results were found, once again, in the "NON-POWER" group which included this genotype (ACE II/ID + ACTN3 XX) compared to the "POWER" group (ACE DD + ACTN3 RR/RX). Several studies in which the training program was not performed but where the same strength test was used in older women [15,36,37] failed to find a relationship with the ACTN3 genotype, which is similar to the results found in the first measurement performed. Kikuchi et al [38] also performed the Chair Stand Test, without training, and failed to find a difference attributable to the genotype in the group of women analyzed.…”
Section: Discussionsupporting
confidence: 75%
“…In the combined analysis of genes, improved results were found, once again, in the "NON-POWER" group which included this genotype (ACE II/ID + ACTN3 XX) compared to the "POWER" group (ACE DD + ACTN3 RR/RX). Several studies in which the training program was not performed but where the same strength test was used in older women [15,36,37] failed to find a relationship with the ACTN3 genotype, which is similar to the results found in the first measurement performed. Kikuchi et al [38] also performed the Chair Stand Test, without training, and failed to find a difference attributable to the genotype in the group of women analyzed.…”
Section: Discussionsupporting
confidence: 75%
“…Actn3 KO mice presented lower bone mineral density and bone formation rates per unit of bone surface when compared to WT littermates, suggesting that the lack of α-actinin-3 is associated with disruptions in mineralisation and resorption (Yang et al 2011) . α-actinin-3 deficient humans also presented with lower levels of bone mineral density (Yang et al 2011;Min et al 2016), as well as higher values of serum bone remodelling markers than R allele carriers at rest (Levinger et al 2017). This information suggests that XX genotype may contribute to a higher likelihood of bone injury during exercise but to the date, there is no evidence for an effect of the ACTN3 genotype on the risk or severity of bone injuries during exercise activities.…”
Section: α-Actinin-3 Deficiency and Other Types Of Injuriesmentioning
confidence: 95%
“…The authors of this investigation declare that there is no conflict of interest. (Yang et al 2011;Min et al 2016;Levinger et al 2017) (Yang et al 2011) Author Contribution Statement JDC, PH, NE and AL conceived and designed the organization of the review. JDC wrote the manuscript.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…In particular, the R allele of ACTN3 tends to be associated with better maintenance of muscle mass, strength and function ( Delmonico et al, 2008 ), a greater adaptive response to training ( Pereira et al, 2013 ), and is protective against the development of sarcopenia ( Cho et al, 2017 ). There also appears to be a (less robust) relationship between ACTN3 genotype and BMD in the elderly, with the R allele again being protective ( Min et al, 2016 ; Cho et al, 2017 ). It is not clear whether this is due to ACTN3 directly influencing bone metabolism, or whether the increased muscle mass and function of R allele carriers leads to greater bone loading, and therefore BMD maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…A small number of studies have examined the interaction between ACTN3 genotype and BMD loss in elderly populations. Min et al (2016) , for example, reported a significant difference in BMD at both the spine and pelvis between genotypes, with XX and RX genotypes having lower scores than RR genotypes. Cho et al (2017) reported similar findings, although the lower BMD in XX genotypes wasn’t significant after covariate correction ( p = 0.075).…”
Section: Actn3 Genotype and Bone Mineral Density With Agingmentioning
confidence: 99%